2013
DOI: 10.4187/respcare.01887
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula Therapy in Do-Not-Intubate Patients With Hypoxemic Respiratory Distress

Abstract: HFNC can provide adequate oxygenation for many patients with hypoxemic respiratory failure and may be an alternative to NIV for DNI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(115 citation statements)
references
References 20 publications
5
103
1
6
Order By: Relevance
“…This result was consistent with 19 during invasive procedures such as bronchoscopy, 20 and do-not-intubate patients. 21 As in this study the subjects showed relatively low levels of dyspnea (dyspnea score of Ͻ 3 points), low breathing frequency (Ͻ 25 breaths/min), and low heart rate (Ͻ 100 beats/min), one could argue that similar results may have been achieved with only the conventional oxygen therapy. However, it can be reasonably speculated that greater benefits may be obtained with HFNC in patients showing greater degrees of post-extubation respiratory distress.…”
Section: Discussionmentioning
confidence: 80%
“…This result was consistent with 19 during invasive procedures such as bronchoscopy, 20 and do-not-intubate patients. 21 As in this study the subjects showed relatively low levels of dyspnea (dyspnea score of Ͻ 3 points), low breathing frequency (Ͻ 25 breaths/min), and low heart rate (Ͻ 100 beats/min), one could argue that similar results may have been achieved with only the conventional oxygen therapy. However, it can be reasonably speculated that greater benefits may be obtained with HFNC in patients showing greater degrees of post-extubation respiratory distress.…”
Section: Discussionmentioning
confidence: 80%
“…For subjects with acute respiratory failure, multiple comorbidities, and do-not-intubate orders, HFNC may be a useful means of palliation. Peters and colleagues 18 reported that HFNC provided adequate oxygenation for 82% of subjects with do-not-intubate orders without requiring escalation to NIV. To our knowledge, the use of HFNC has not been studied in a palliative population, and further examination is warranted to determine its therapeutic utility.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized trials comparing standard oxygen therapy and HFOS have shown a better patient comfort but no significant difference in gas exchange in post-extubation patients [7,8]. Two retrospective analysis of HFOS in Do-Not-Intubate patients with cancer and respiratory distress have shown that nearly 85% of patients 38 Karakurt et treated with HFOS improved or remained stable but 18% of patients still needed escalation of therapy to NIMV [9,10].…”
Section: High Flow Oxygen Systemmentioning
confidence: 99%